KORELASIANTAR-KARAKTER DAN SIDIK LINTAS ANTARA KARAKTER AGRONOMIDENGAN HASIL KEDELAI Glycine max (L.) Merrill - Hakim, Lukman (Research Center for Biology-Indonesian Institute of Sciences, 2011)
A total of 27 soybean Glycine max (L.) Merrill genotypes including check variety (Kawi) were evaluated on dry land at Ngale Experimental Farm, Ngawi, East Java during early rainy season of 2009/2010. The experiment was conducted in a randomized complete block design with three replications. Plot size was 4 m x 5 m, plant spacing was 40cmx20cm, each hill contained two plants. A correlation and path coefficient analyses were used in order to determine the association among characters and quantify the direct and indirect effects of agronomic traits on seed yield. The study has identified 3 varieties, i.e. Kaba, Wilis and Tanggamus produced the highest yield (>1.6 t/ha) and had good adaptation on dry land. Two varieties (Grobogan and Argomulyo) having large seed size (>15 g/100 seeds), and four varieties,i.e. Tidar, Grobogan, Gepak Ijo and SHR-W60 had early maturity (81days). Therefore, these varieties can be used as source of parents on breeding program. Among the agronomic characters, plant height, number of pods per plant and harvest index were positively and significantly correlated with grain yield. The direct effect of plant height, number of pods per plant and harvest index to grain yield as indicated by path coefficient were the highest, while other causal effects to grain yield were small or negative. Based on both analyses, soybean genotypes with high grain yield should have sufficient plant height, high number of pods per plant and high harvest index. Therefore, plant height, number of pods per plant and harvest index can be suggested for selection criteria in selecting high yield soybean genotypes on dry land.